2014
DOI: 10.1155/2014/674579
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Single-Site Surgery for Female-to-Male Transsexuals: Preliminary Experience

Abstract: Hysterectomy with bilateral salpingo-oophorectomy is a part of gender reassignment surgery for the treatment of female-to-male transsexualism. Over the last years many efforts were made in order to reduce invasiveness of laparoscopic and robotic surgery such as the introduction of single-site approach. We report our preliminary experience on single-site robotic hysterectomy for cross-sex reassignment surgery. Our data suggest that single-site robotic hysterectomy is feasible and safe in female-to-male transsex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Three studies (Lopez et al [ 20 ], Jayakumaran et al [ 16 ], and Chien-Wen et al [ 22 ]) did not report this variable. Bagliolo et al [ 17 ] reported a minor postoperative complication in one case: vaginal bleeding. Bagliolo et al [ 21 ] described only one grade II complication (according to the Clavien–Dindo classification [ 13 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies (Lopez et al [ 20 ], Jayakumaran et al [ 16 ], and Chien-Wen et al [ 22 ]) did not report this variable. Bagliolo et al [ 17 ] reported a minor postoperative complication in one case: vaginal bleeding. Bagliolo et al [ 21 ] described only one grade II complication (according to the Clavien–Dindo classification [ 13 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The studies included 1 controlled clinical trial (16), 4 retrospective cohorts (8,9,17,18), 2 prospective cohorts (19,20), 1 case report (14), and 3 case series (20)(21)(22). The studies were conducted in the United States (8,9) Czech Republic (15)(16)(17), Italy (14,19), France (18), The Netherlands (23), Germany (20), and Belgium (21).…”
Section: Resultsmentioning
confidence: 99%
“…Laparoscopic hysterectomy: In a prospective study of 10 male transsexual patients, Lazard et al (19) report that single point access offers advantages over conventional laparoscopic technique because of reduced postoperative pain, faster return to normal activity and better cosmetic results. On the other hand, Bogliolo et al (23) performed robotic laparoscopic hysterectomy in a case series that included 10 patients. It is considered to be safe and to be associated with good prognosis in terms of quality of life.…”
Section: Resultsmentioning
confidence: 99%